Pilot study of extended-release lorcaserin for cocaine use disorder among men who have sex with men: A double-blind, placebo-controlled randomized trial. - Glenn-Milo Santos; Janet Ikeda; Phillip Coffin; John E Walker; Tim Matheson; Matthew McLaughlin; Jennifer Jain; Eric Vittinghoff; Steven L Batki (PLoS ONE)
Objective To determine if men who have sex with men (MSM) with cocaine use disorder (CUD) and actively-using cocaine could be enrolled and retained in a pharmacologic intervention trial of lorcaserin-a novel 5-HT2cR agonist-and determine the degree to which participants would adhere to study procedures. Methods This was a phase II randomized, double-blind, placebo-controlled pilot study with 2:1 random parallel group assignment to daily extended-release oral lorcaserin 20 mg versus placebo (clinicaltrials.gov identifier-NCT03192995). Twenty-two of a planned 45 cisgender MSM with CUD were enrolled and had weekly follow-up visits during a 12-week treatment period, with substance use counseling, urine specimen collection, and completion of audio-computer assisted self-interview (ACASI) behavioral risk assessments. Adherence was measured by medication event monitoring systems (MEMS) caps and self-report. This study was terminated early because of an FDA safety alert for lorcaserin's long-term use. Results Eighty-six percent completed the trial, with 82% of weekly study follow-up visits completed. Adherence was 55.3% (lorcaserin 51.6% vs. placebo 66.2%) by MEMS cap and 56.9% (56.5% vs. placebo 57.9%) by self-report and did not differ significantly by treatment assignment. Intention-to-treat analyses (ITT) did not show differences in cocaine positivity by urine screen between the lorcaserin and placebo groups by 12 week follow-up (incidence risk ratio [IRR]: 0.96; 95%CI = 0.24-3.82, P = 0.95). However, self-reported cocaine use in timeline follow-back declined more significantly in the lorcaserin group compared to placebo (IRR: 0.66; 95%CI = 0.49-0.88; P = 0.004). Conclusion We found that it is feasible, acceptable, and tolerable to conduct a placebo-controlled pharmacologic trial for MSM with CUD who are actively using cocaine. Lorcaserin was not associated with significant reductions in cocaine use by urine testing, but was associated with significant reductions in self-reported cocaine use. Future research may be needed to continue to explore the potential utility of 5-HT2cR agonists.